حكم الصلاة على أجزاء الميت في الفقه الإسلامي: The Ruling on Praying over the Body Parts of the Deceased in Islamic Jurisprudence - Hammad, Hamza Abed al Karim (Jurnal Fiqh, 2024)
This research aims to determine the most proper opinion on the issue of praying over body parts of the dead under Islamic jurisprudence. The research followed the descriptive and analytical method by describing the issue practically, then the jurisprudential study of each form of the issue. The research concluded that the opinion that says washing, shrouding, and praying over any body part of the dead person, whether few or many, is preferred. The scholars differed on the issue of praying over the body parts of a person whose death is certain, with three opinions. The researcher presented these opinions and their evidence and discussed it in depth, then concluded with the preponderance of the opinion that says washing, shrouding, and praying over any found body parts of the dead person, whether those parts are few or many in light of the possibilities mentioned in the research. Keywords: Islamic funeral prayer (Salat al-Janazah), Islamic Jurisprudence, Body parts of the dead.